LABORATORY DIAGNOSIS OF ASCARIS LUMBRICOIDES INFESTATION IN PAEDIATRIC POPULATION IN TWO MUNICIPALITIES IN BOSNIA AND HERZEGOVINA - Rebić, Velma; Hadzimuratovic, Emina; Vincevic-Smajlovic, Sajra; Abduzaimovic, Kadrija; Kahvic, Selma; Aljicevic, Mufida; Dzubur-Alic, Amela; Supur, Edna (Sanamed, 2024)
Introduction: Ascaris lumbricoides is a widely spread helminthic infection, predominantly affecting children, making them the most commonly infected population group. The objective of this study is to assess the prevalence of Ascaris lumbricoides infestation in two municipalities, Tešanj and Maglaj, and to investigate the occurrence of Ascaris lumbricoides infections in the pediatric population, focusing particularly on preschool children.Materials and Methods: The study involved the collection of 1409 fecal samples from the Tešanj and Maglaj areas, gathered over a 6-month period, spanning from September 2018 to February 2019. The processing of these samples was conducted in the Microbiology Laboratory of Tešanj General Hospital.Results: Out of the total 1409 samples, 129 (9.16%) tested positive for Ascaris lumbricoides infestation. In Tešanj, where 1198 samples were collected, 106 (8.85%) tested positive, while in Maglaj, 211 samples were collected, with 23 (10.9%) testing positive. Notably, the majority of positive cases in both Tešanj and Maglaj were preschool-age children, accounting for 88.68% and 86.96%, respectively. The study did not identify any statistically significant correlation between age and gender distribution among those with positive test results in either Tešanj or Maglaj.Conclusion: Based on the study results, which have highlighted the infestation of preschool children with Ascaris lumbricoides in two municipalities in our country, it is imperative to implement preventive measures aimed at reducing the incidence of infection.
Keywords: Ascaris lumbricoides; Ascariasis; infestation; children